Detection of Occult Patent Ductus Arteriosus Through Teleradiology in a Forward-Deployed Setting - Ryan Dinnen; Anthony Cossetti; Oskar Kizhner (Military Medicine, 2026)
Abstract Patent ductus arteriosus (PDA) is a congenital cardiac anomaly most often diagnosed in infancy or childhood and infrequently detected in adulthood. In young adults, clinical and radiographic manifestations may be subtle and nonspecific, leading to delayed diagnosis. We report a case involving a 22-year-old previously healthy active duty female service member who presented with pleuritic chest pain at a forward-deployed medical facility in Djibouti, Africa. Chest radiographs were transmitted via teleradiology to a remotely located radiologist for interpretation. The radiologist identified discrete but abnormal findings consistent with pulmonary edema, including faint, patchy alveolar opacities, fine Kerley B lines at the lung bases, mildly prominent interlobar fissures, and trace bilateral pleural effusions, with an otherwise normal cardiac silhouette. Based on these findings, the radiologist recommended advanced cross-sectional imaging. Follow-up CT pulmonary angiography, obtained to rule out pulmonary embolism, identified a PDA with associated pulmonary overcirculation and left pulmonary artery enlargement, suggestive of pulmonary hypertension. This case demonstrates the critical role of teleradiology in extending expert imaging interpretation to austere, forward-deployed environments where on-site radiology subspecialty support is unavailable. The identification of subtle radiographic findings by a remote radiologist prompted further diagnostic evaluation, facilitating the diagnosis of occult congenital heart disease and appropriate medical evacuation.